Compress Onions (Allium Cepa) As A Nonpharmacological Therapy in Febris Toddlers - Erda, Roza; Badar, Mawardi; Yunaspi, Didi; Oktavina, Yanti (Universitas Aisyah Pringsewu, 2021)
Cases of fever in toddlers are a health problem that continues to increase. WHO statistics show there are 18-34 million cases per year. One of the nonpharmacological treatments that can be done to lower body temperature in toddlers is to compress onions. This study aims to find out the effect of giving onion compresses as a decrease in body temperature in toddlers aged 1-5 years with febris in the Tanjung Sengkuang Health Center Work Area of Batam City in 2020. This research design uses experimental Quasi with a one group pre-test and post-test design approach. Sample withdrawal techniques use purposive sampling. The respondents in this study were 32 respondents. Data analysis techniques To test the hypothesis is the Paired Sample T-Test test. The results of the data analysis were obtained that after the therapy of The Onion Compress experienced a decrease in body temperature by (p-value less than 0.05). Conclusion: onion compresses can be used as an alternative to reduce fever in toddlers. The authors suggest the need to increase the role of nurses in Puskesmas by involving families to utilize alternative therapies based on evidence from research results and evidence.